PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) - Lisa Ayu Hidayati; Zulfikri Suleman; Yunin dyawati (Jurnal Media Sosiologi (JMS), 2020)
This thesis is titled "Community Based Water Supply and Sanitation (PAMSIMAS) in Gunung Kerto Village, Tanjung Sakti Pumi District, Lahat Regency". This study examines the background of the shortage of clean water from the people of Gunung Kerto Village who received a community-based water supply and sanitation program (PAMSIMAS). The purpose of this study is to know and analyze the description of community-based water supply and sanitation (PAMSIMAS). This research is a descriptive qualitative research, this research was conducted with data collection techniques through observation, in-depth interviews and documentation. The results showed that the problem of lack of clean water in the community of Gunung Kerto village was overcome by the existence of a government program in the form of community-based water supply and sanitation (PAMSIMAS), which was carried out through community empowerment and also involving community participation starting from the planning, implementation, results , evaluation until maintenance for the sustainability of the Pamsimas program. From the results of the study, it is known how the description of the process of community-based water supply and sanitation, and the participation and responsibility of the Gunung Kerto Village community for the programs provided by the government require steps to be implemented as they should. Because this can be seen from all stages during the development process of Pamsimas.